The Portable Carbon Monoxide (CO) and Hydrocarbons (HC) Gas Detection System in The Car Cabin Uses The MQ-9 and TGS 2610 Sensors - Mochamad Irwan Nari; Januar Ajie Laksono; Bachrul Ulum Hidayat; Ahmad Robiul Awal Udin (Future Science, 2021)
The increase in the number of vehicles especially cars causes the air environment to look polluted. This is caused by vehicle exhaust gases that can affect the level of human health. Harmful gases such as carbon dioxide (CO) and hydrocarbon (HC) can also enter the car cabin, making people inside feel suffocated and even death. To find out the presence of these gases, a monitoring system prototype is made which is placed in the car cabin. This system consists of input in the form of an MQ-9 sensor and a TGS2610 sensor. The readings of these sensors are processed by Arduino Uno. The system output is made in the form of a buzzer and LCD. Tests carried out on the car cabin area are divided into three, namely front, middle, and rear. The results of the 6 tests show that the smallest percentage of CO errors is 8% in the middle area and HC of 8.7% in the rear area of the car cabin.